Antimicrobial resistance - moving forward? - Marta Lomazzi; Michael Moore; April Johnson; Manica Balasegaram; Bettina Borisch (BMC, 2019)
Abstract Background When microorganisms (such as bacteria or viruses) are highly exposed to antimicrobial drugs, they can develop the capacity to defeat the drugs designed to eradicate them. Long-term accumulation of adaptations to survive drug exposure can lead to the development of antimicrobial resistance (AMR). The success of antibiotics has led to their widespread overuse and misuse in humans, animals and plants. Main text AMR is a global concern and solutions are not vertical actions in a single buy business model. Even if a transectoral approach is key, there is a lack of multi-disciplinary partnerships that allow for strategic cooperation between different sectors such as the pharmaceutical industry, agro-alimentary complex, patient care and education, NGOs and research and development. Global public health voices should lead this integration to align the progress of existing AMR successes. Maintaining the public's trust in preventive medicine, health systems and food production safety, together with public health driven, non-profit drug development, is a key factor. In its "Call for integrated action on AMR", signed by about 70 national and international organizations the World Federation of Public Health Associations (WFPHA) called "on all governments, the private sector, non-governmental organizations, health professionals, public and private research organizations, and all stakeholders to ensure that public health remains at the centre of all policy and scientific endeavours in the field of antimicrobial resistance". Conclusions The "Global Charter for the Public's Health", developed by the WFPHA in association with WHO, is proposed in this article as a tool for implementation of complex public health actions such as AMR.